2018
DOI: 10.3390/galaxies7010005
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Helical Magnetic Fields Associated with AGN Jets and the Action of a Cosmic Battery

Abstract: Theoretical models for the electromagnetic launching of astrophysical jets have long indicated that this process should generate helical magnetic fields, which should then propagate outward with the jet plasma. Polarization observations of jets are key for testing this idea, since they provide direct information about the magnetic field structures in the synchrotron-emitting radio jets. Together with Faraday rotation measurements, it is possible in some cases to reconstruct the three-dimensional magnetic-field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 42 publications
2
29
0
Order By: Relevance
“…This can be reconciled by the existence of partial ordering of the magnetic field. For example, the partial ordering along the jet direction inferred from the mean EVPA can be the consequence of compression of the turbulent plasma by a shock (e.g., Hughes et al 1985;Cawthorne 2006;Marscher 2014) or the superposition of turbulence and a helical magnetic field (e.g., Raiteri et al 2010;Gabuzda 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be reconciled by the existence of partial ordering of the magnetic field. For example, the partial ordering along the jet direction inferred from the mean EVPA can be the consequence of compression of the turbulent plasma by a shock (e.g., Hughes et al 1985;Cawthorne 2006;Marscher 2014) or the superposition of turbulence and a helical magnetic field (e.g., Raiteri et al 2010;Gabuzda 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Funding for the DPAC has been provided by national institutions, in particular the institutions participating in the Gaia Multilateral Agreement. This research made use of Astropy, 8 a community-developed core Python package for Astronomy (Astropy Collaboration et al 2013, 2018, and astroquery, an astronomical web-querying package in Python (Ginsburg et al 2019).…”
mentioning
confidence: 99%
“…Studies in the slab configuration have shown significant particle acceleration. However, the slab configuration cannot be applied to astrophysical jets, since helical magnetic fields are thought to be the dominant magnetic field morphology close to the jet collimation/launching point (e.g., Tchekhovskoy 2015), as evidenced by observations (e.g., Hawley et al 2015;Gabuzda 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The collected data indicate that AGN jets reveal strong signs of the spine-sheath jet structure with a central spine of orthogonal magnetic field and a sheath of longitudinal magnetic field along the edges of the jet [26]. They suggest that the inner region of the jet spine consists of a low-density and fast-moving gas, while the outer region of the jet sheath consists of a denser and slower moving gas [27] The spine-sheath jet structure can also be explained by the coaxial cable proposed by Gabuzda [28] [29]. Like coaxial cable with the inner conductor and the outer shield sharing a geometric axis, an AGN jet has an inward current along its axis and an outward current in a more extended sheath-like region surrounding the jet.…”
Section: Agn Based On Supermassive Superstarmentioning
confidence: 97%